PENGEMBANGAN MODEL PERENCANAAN HIMPUNAN DATA DAN APLIKASI INSTRUMENTASI BERBASIS POLA TUJUH BELAS PLUS PADA GURU BK/KONSELOR SMP DI KABUPATEN BONDOWOSO - Indra Kusuma; Sapto Mei Budiyanto (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
The main target of the research is to show that planning is the most important stages of management function, mainly to face exsternal environment that changed dynamically. The main topic on this research was focused on the certain elements from planning process and the process that have very closed relation with the problem solving and also the program development of counseling service at school. The Planning model for counceling activity by using seventeen plus pattern approach to be very urgent to be done by guiding and counceling teachers in order the implantation is in line with the students’ need at the field.From the introduction study can be concluded that in general the Bk/guiding and counceling teachers at Junior High School/SMP at Bondowoso is still having not variant data that should be owned for conducting guiding and counceling service at school. In general, the guiding and counceling teachers SMP/Jumior High School at Bondowoso felt important and even very important for having data collection and instrumentation application for running on the duty for conducting guiding and counceling service at school, with average score: 3,23.Besides that, it can be explained that conducting evaluation of data collecting and the existing of instrumentation application nowadays, it can be concluded that it was still very low in general with the average score = 1,14. While, it was linked with the need of model development for data compilation activity planning and instrumentation application were found that guiding and counceling’s teachers very needed in general with the average score = 4,28. While it was linled with the assessment of model development of data compilation activity planning and instrumentation application that were promoted, it was found that guiding and counceling’s teachers gave very good assessment in general with the average score = 4,47.